Oil Bunkering and Insecurity in Rivers State - Dagogo; Doctor Farah (Zien Journals, 2022)
This study is focused on the burden of oil bunkering in Rivers State. When a resource like crude oil is constitutionally made to be collectively owned, it is only expected of the State to protect it and ensure that it is equitably distributed to the benefit of all. The activity of oil bunkering is increasing the problem of insecurity in Rivers State. Consequently, this study aimed to examine the nature and dimension of the problems of oil bunkering, how it has escalated insecurity in Rivers State with the intent of finding workable solutions to control it for crude oil to fully contribute to our national development. The paper is anchored on both primary and secondary sources of data. Besides, the Political Economy approach was used to guide this study. The data collected through secondary sources were thoroughly subjected to inductive approach of data analysis. The paper revealed that there is a prevalence of oil bunkering and insecurity in Rivers State; and this reality is affecting the economy of Rivers State and Nigeria at large; greed is the strongest factor causing the existence of oil bunkering; and some of the ruling elite are accomplices in oil bunkering crime to the underdevelopment of Rivers State, thus giving the federal government a big challenge to curb this phenomenon. Consequently, the study recommended strict measures and their application to stop oil bunkering; punitive measures to control oil bunkering; provision of employment for the youths of Rivers State; dissuading our youths from oil bunkering, and adequately equipping security operatives to crush oil bunkering; and the use of peace dialogue
Keywords: Oil Bunkering; Insecurity; Underdevelopment; National Development